Improving efficiency of customer requirements classification on autonomous vehicle by natural language processing - Wang, Hoa; Asrul, Adam; Han, Fengrong (Elsevier, 2020)
Safety is critical for autonomous vehicle, therefore quality management system method is crucial for the risks that may impact human beings. Quality management system help identify customer requirements and finally meet them. Customer requirements also include other aspects that customers or stakeholders are most concerned. Although many researches on customer perception had been done, they do not include all aspect of the requirements toward autonomous vehicle. Furthermore, they are most in text format or will be transfer to text format that convenient to store and read. In front of the large amount text data, classifying them become time and costs consuming. The customer requirements on autonomous vehicle are summarized and allocated in different categories. The natural language processing method is applied in this paper. This method shows its efficiency on dealing with customer requirements. The results provide valuable reference for autonomous vehicle developer and top managemen